MicroRNA-15b participates in the development of peripheral arterial disease by modulating the growth of vascular smooth muscle cells - Sun, Yong (Exp Ther Med, 2019)
As an atherosclerotic disease, the process of peripheral arterial disease (PAD) is complicated and includes the abnormal proliferation of vascular smooth muscle. The current study aimed to determine the role of microRNA-15b (miR-15b) in the development of PAD and its associated mechanisms. Human vascular smooth muscle cells (hVSMCs) were used in the current study. To assess the effects of miR-15b on hVSMCs, miR-15b was up- or downregulated in hVSMCs using miR-15b mimics or miR-15b inhibitors respectively. Cell viability, migration and apoptosis were then determined via MTT, transwell and flow cytometry assays, respectively. TargetScan bioinformatics software was utilized to predict the targets of miR-15b, and the binding sites between insulin growth factor 1 receptor (IGF1R) and miR-15b were confirmed by dual-luciferase reporter assay. The results reveled that the miR-15b mimic significantly reduced hVSMC cell viability and migration, and promoted cell apoptosis. However, the opposite effect was observed following miR-15b inhibitor transfection. It was also determined that miR-15b directly targeted IGF1R and negatively regulated its expression in hVSMCs. Additionally, the results demonstrated that the miR-15b mimic inhibited the PI3K/AKT signaling pathway in hVSMCs, whereas the miR-15b inhibitor promoted it. Furthermore, the results indicated that the effect of the miR-15b mimic on hVSMCs was reversed by IGF1R overexpression. In conclusion, the data indicated that miR-15b participated in the occurrence and development of PAD by modulating hVSMC proliferation, apoptosis and migration via the regulation of IGF1R expression.